(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2025)
The paper talks about the practical methods of implementing social-emotional learning (SEL) in the school curriculum to assist students’ mental health and interpersonal relationships. As there is increasing recognition of the essential role of mental well-being in academic success, schools are more willing to include SEL. The article offers teachers practical advice, including creating a positive classroom environment, employing group work, and teaching mindfulness. Moreover, the article emphasizes the significance of family and community collaboration in reinforcing SEL initiatives. By incorporating these practices into everyday instruction, educators can establish a complete learning atmosphere that reinforces learners’ emotional intelligence, resilience, and interpersonal skills.